2010
DOI: 10.1097/rli.0b013e3181ed1b3b
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasound Contrast Agent Targeted to P-Selectin Detects Activated Platelets at Supra-Arterial Shear Flow Conditions

Abstract: Objectives To evaluate targeting of a microbubble contrast agent to platelets under high shear flow using the natural selectin ligand sialyl Lewisa. Materials and Methods Biotinylated polyacrylamide Sialyl Lewisa or biotinylated carbohydrate-free polymer (used as a control) were attached to biotinylated microbubbles via a streptavidin linker. Activated human platelets were isolated and attached to fibrinogen-coated culture dishes. Fibrinogen-coated dishes without platelets or platelet dishes blocked by an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…We employed parallel plate flow chambers, which are used to investigate the fluid shear rates, particle size, concentration and ligand and target site density requirements for promoting microbubble adhesion [9,42,[57][58][59][60][61][62]. Flow experiments initially conducted with microbubbles suspended in cell media demonstrated that microbubble binding was almost completely inhibited under this condition, likely due to media blocking microbubble-conjugated antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…We employed parallel plate flow chambers, which are used to investigate the fluid shear rates, particle size, concentration and ligand and target site density requirements for promoting microbubble adhesion [9,42,[57][58][59][60][61][62]. Flow experiments initially conducted with microbubbles suspended in cell media demonstrated that microbubble binding was almost completely inhibited under this condition, likely due to media blocking microbubble-conjugated antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Drugloaded microbubbles would be attractive ultrasoundresponsive drug carriers. The approach that drugloaded microbubbles or phase-shift nanoparticles be beneficial for drug targeting to intravascular targets would be a dramatic ultrasound-responsive drug transportation [88,89,[91][92][93].…”
Section: Inertial Cavitation Stable Cavitation Us Usmentioning
confidence: 99%
“…αvβ3 integrin, cyclic arginine-glycineaspartic acid (RGD) peptide and knottin peptides have been targeted with microbubbles [28,29]. Clot imaging is important for myocardial infarction, deep venous thrombosis/pulmonary embolism and stroke assessment with Microbubble targeting to glycoprotein IIb-IIIa receptors and P-selectin ligand [30].…”
Section: Molecular Imagingmentioning
confidence: 99%